Nutritional and sensory values of muscles and liver from cultured Baung Hemibagrus nemurus (Valenciennes, 1840) and African Catfish Clarias gariepinus (Burchell, 1822) - Abdi, Hesamoddin (2014)
The most popular fish consumed in Malaysia are from the catfish families of Clariidae,Bagridae and Pangasiidae. In this study, two of these most commonly cultured and consumed catfishes, Asian redtail, Hemibagrus nemurus and African catfish, Clarias gariepinus were evaluated for chemical, nutritional and organoleptic properties. Fresh catfishes bought from local farm and wholesellers were transported to laboratory at Department of Aquaculture, Faculty of Agriculture, Universiti Putra Malaysia, Serdang,Selangor. Muscle was cut and analysed for moisture, ashes, protein and total fat contents as well as evaluation for fatty acid and amino acid profile. The same process was carried out for liver except for the profiling of amino acid. This study indicates a good nutritional condition for all fish samples (CF >1). Results were compared between male and female H. nemurus and C. gariepinus. Female H.nemurus and C. gariepinus contained the lowest protein and fat. On the other hand, moisture found to be the highest in both females H. nemurus and C. gariepinus. Male of H. nemurus contained the highest amount of fat and ash. Liver of female H. nemurus contained the highest amount of ash and crude lipid but with lowest amount of moisture. Male C. gariepinus had the lowest amount of protein, ash and crude lipid. Moisture was found to be the highest in male C. gariepinus. The major fatty acids in Asian redtail catfish and African catfish muscle were C14:0, C16:0, C16:1, C18:0, C18:1n-9, C18:2n-6, C18:3n-3, C20:4n-6, C24:1, C20:5n-3, C22:5n-3 and C22:6n-3. All the above mentioned fatty acids were found in the liver of Asian redtail catfish and African catfish with the addition of C12:0, C15:0 and C17:0. The most abundant fatty acids in both species for liver and muscle were oleic acid (18:1n-9) and palmitic acid (16:0). Levels of aspartic acid, glutamic acid and threonine were significantly different between the two species and sexes as well (P < 0.05). Significant variations were observed in body composition, amino acid, fatty acids and sensorial properties of the two catfish species. The amino acid profile showed both catfish species to be good sources of essential amino acids except for tryptophan. Asian redtail and African catfish contained high levels of omega-3 and omega-6 PUFAs, respectively. Male and female H. nemurus found to have better color and taste which male H. nemurus showing the highest acceptance by panelists. In conclusion, this study showed that H. nemurus has better meat quality as compared to C. gariepinus.